Moment‐based boundary conditions for straight on‐grid boundaries in three‐dimensional lattice Boltzmann simulations. (2nd June 2020) - Krastins, Ivars; Kao, Andrew; Pericleous, Koulis; Reis, Timothy
Summary: In this article, moment‐based boundary conditions for the lattice Boltzmann method are extended to three dimensions. Boundary conditions for velocity and pressure are explicitly derived for straight on‐grid boundaries for the D3Q19 lattice. The method is compared against the bounce‐back scheme using both single and two relaxation time collision schemes. The method is verified using classical benchmark test cases. The results show very good agreement with the data found in the literature. It is confirmed from the results that the derived moment‐based boundary scheme is of second‐order accuracy in grid spacing and does not produce numerical slip, and therefore offers a transparent way of accurately prescribing velocity and pressure boundaries that are aligned with grid points in three‐dimensional. Abstract : We present for the first time the extension of moment‐based boundary conditions for lattice Boltzmann methods to three‐dimensional lattices. Pressure and velocity boundary conditions are considered at faces, edges, and corners. Numerical results obtained with this method are in excellent agreement with benchmark data and analytical solutions, they exhibit second‐order spatial convergence, and computations confirm the errors are viscosity‐independent.